Customer Perception of the Use Application Sharia Pawnshops Reviewed from Age Groups: A Study at the Meulaboh Branch of Sharia Pawnshops - Irayana, Rizka; Rinaldi, Mikhral; Hendrawan, Yoni (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze customer perceptions of the use of the Sharia Pawnshop application, focusing on the differences between the young age group (18-35 years) and the elderly age group (over 50 years) at the Sharia Pawnshop Branch in Meulaboh. The digital transformation in Sharia financial services has changed the way the community accesses services; however, the adoption of this digital application shows significant differences based on age. The research method used is descriptive qualitative, with data collection through semi-structured interviews and direct observation of 23 customers. The results indicate that younger customers tend to be more positive and active in using the application, utilizing features such as online pawn booking and installment payments. In contrast, elderly customers show high resistance, attributed to limited technological knowledge and concerns about data security. Support from staff in the digitalization process has proven to be crucial in bridging the existing digital divide. This study emphasizes the need for an educational and inclusive approach in digital transformation so that all age groups can benefit from Sharia financial services in the digital era. The findings are expected to provide strategic recommendations for the Sharia Pawnshop in designing more adaptive and inclusive services.